2011
DOI: 10.4314/pamj.v8i1.71064
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and birth prevalence of birth defects and inborn errors of metabolism in Al Ahsa, Saudi Arabia

Abstract: BackgroundBirth defects and inborn errors of metabolism are related to variable poor perinatal and neonatal outcomes. Our aim was to explore the pattern and prevalence of birth defects and metabolic birth errors in Al-Ahsa Governorate in the Eastern Province of Saudi Arabia.MethodsThis retrospective case control study was done from April 2006 to 2009. Children with any birth defect or metabolic errors of metabolism at birth or in the neonatology section were our sample for study. Control group was randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
2
27
0
1
Order By: Relevance
“…However, it must be noted that the high level of consanguinity is comparable to that among patients who have been reported with other metabolic disorders in Saudi Arabia. 27 Biochemical confirmation of HMGCL deficiency was done by urine organic analysis for all of our patients and 94% of TMS suggested the initial diagnosis. We do not recommend enzymatic essay from skin fibroblast culture or liver tissue, as the metabolic screening is consistent with the biochemical diagnosis.…”
Section: Discussionmentioning
confidence: 89%
“…However, it must be noted that the high level of consanguinity is comparable to that among patients who have been reported with other metabolic disorders in Saudi Arabia. 27 Biochemical confirmation of HMGCL deficiency was done by urine organic analysis for all of our patients and 94% of TMS suggested the initial diagnosis. We do not recommend enzymatic essay from skin fibroblast culture or liver tissue, as the metabolic screening is consistent with the biochemical diagnosis.…”
Section: Discussionmentioning
confidence: 89%
“…diabetes and rubella) , lack of environmental protection policies, unsafe working conditions during pregnancy, medication use during pregnancy, common use of home remedies of unknown composition and chemical household cleaners [5]. In addition, growth restriction, preterm delivery, mother's age and weight during pregnancy and parental consanguinity are also associated with birth defects [7,8]. Furthermore, it has been reported that there is an association between environmental exposures such as air pollution, alcohol consumption, environmental tobacco smoking, radiation, pesticides and pregnancy outcomes such as pregnancy loss, stillbirth, fetal growth, preterm birth and congenital anomalies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…26 Genetic risk factor plays a fundamental role; Loss of the Sox2 gene was observed in most cases of NTDs. 2 Positive family history of NTDs was in about 10%, and they increase markedly if there were two previously affected family members. 2 The prevalence of NTDs at birth varied markedly in each country and race.…”
Section: Introductionmentioning
confidence: 99%
“…2 Positive family history of NTDs was in about 10%, and they increase markedly if there were two previously affected family members. 2 The prevalence of NTDs at birth varied markedly in each country and race. It ranges from as high as 1% in China, to approximately 1 case in 5000 or less in Norway and Sweden.…”
Section: Introductionmentioning
confidence: 99%